Reading in English by non-native children: types of miscues and the L1 influence - Huszti Ilona; Густі Ілона (My University, 2020)
Abstract. The research described in this paper was carried out among eleven-year-olds in a bilingual context. The learners were native Hungarian and Ukrainian children who studied English as a foreign language (EFL) in Berehove, a small provincial town in the south-west of Ukraine. The population of the town is multi-national and multilingual. The various languages of the nations living side by side have evident impact on each other. The main aim of conducting the investigation was to obtain empirical evidence whether the two languages also influence the acquisition of a third one when learners learn a language as a foreign one.
https://openscilab.org/wp-content/uploads/2020/11/suchasni-vikliki-i-aktualni-problemi-nauki-osviti-ta-virobnictva_2020_11_13_tezy.pdf
Keywords: hangos olvasás angolul; olvasási hibák típusai; az anyanyelv hatása; reading in english; non-native children; foreign language learners